Animal Studies of Colon Carcinogenesis and Altered Epithelial Cell Differentiation - Hugh J Freeman (Canadian Journal of Gastroenterology)
Chronic inflammatory bowel disease (IBD) appears to predispose to subsequent colon cancer. Factors that influence the degree of this risk require definition since the reported incidence of malignant change varies widely. Differing environmental factors such as diet may be critical, and several approaches have been used to explore the role of specific variables in colon cancer pathogenesis; one has employed the use of animal models. Naturally occurring models of colon cancer exist including cotton-topped tamarins with colitis. Best studied, however, are animal models of colon cancer induced with specific chemical carcinogens. Cycasin and hydrazine derivatives, eg, 1,2-dimethylhydrazine, are most widely used. After parenteral administration of an active carcinogen, metabolic activation occurs, resulting in colonic adenocarcinomas. Sessile and polypoid neoplasms may be induced, particularly in the distal colon, similar to human colon cancer. Using this model, the effect of differing dietary and therapeutic variables has been explored. Studies with purified single dietary fibres, such as microcrystalline cellulose and hemicellulose, but not pectin, have demonstrated reduced numbers of colonic tumours; these in vivo observations correlate with in vitro effects of fibres on rat luminal and fecal mutagenic activities. Specific therapies used in IBD have also been evaluated - metronidazole, for example, a bacterial mutagen, enhances the development of chemically induced rodent colon cancer. In addition, a significant increase in colonic tumour development occurs after intestinal resection or bypass, two procedures used in the surgical management of IBD. In this setting, surgical sutures, particularly nonabsorbable materials including stainless steel, may play a critical role. Although the extent and duration of disease in patients with chronic IBD may be important in colon cancer pathogenesis, other variables, including diet and treatment, may be critical modulating factors.